Rickettsia in mosquitoes, Yangzhou, China - Jilei Zhang; Patrick John Kelly; Guangwu Lu; Luis Cruz-Martinez; Chengming Wang (Emerging Microbes and Infections, 2016)
Emerging Microbes & Infections (2016) 5, e108; doi:10.1038/emi.2016.107; published online 12 October 2016